Nitrogen Use Efficiency of Local and National Aromatic Rice Varieties in Indonesia - Chairunnisak, Chairunnisak; Sugiyanta, Sugiyanta; Santosa, Edi (Journal of Tropical Crop Science, 2018)
Nitrogen use efficiency (NUE) is a necessitate in order to enhance sustainable rice farming in Indonesia. Thus, objective of present research was to evaluate NUE of local and national Indonesian superior aromatic rice treated with different levels of nitrogen fertilizer (N). Planting plot was arranged using five levels of N as the main plot, i.e; 0, 45, 90, 135 and 180 kg ha-1; and two rice varieties as subplot, i.e: Sigupai Abdya (local) and Inpari 23 Bantul (national). The results showed application 180 kg N ha-1 to Sigupai  Abdya significantly increased the plant height. However, it also postponed the flowering time. Inpari 23 Bantul treated with 180 kg N ha-1 produced the highest number of tillers. Combination of 90 kg N ha-1 with Sigupai Abdya variety significantly reduced the number of empty grains. Sigupai Abdya variety has a higher number of grains per panicle and sampling plot yield than Inpari 23 Bantul, and  dosage 90 kg N ha-1 increases grain yield per clump also sampling plot yield significantly. Nitrogen at 180 kg N ha-1 made Sigupai Abdya variety has high N content and absorption N in primordia phase, and the Inpari 23 Bantul variety had grain with high N content. Nitrogen at 90 kg ha-1 caused Sigupai Abdya variety at primordia phase had NUE higher than Inpari 23 Bantul. This study showed that local variety Sigupai Abdya is suitable for development as rice with low input NKeywords: Aceh aromatic, low input, nitrogen dose, N uptake, Oryza sativa L.